2017
DOI: 10.1007/s00535-017-1326-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of golimumab 52-week maintenance therapy in Japanese patients with moderate to severely active ulcerative colitis: a phase 3, double-blind, randomized, placebo-controlled study-(PURSUIT-J study)

Abstract: BackgroundThe global phase 3 studies of golimumab [PURSUIT-SC and PURSUIT-maintenance (M)], an anti-tumor necrosis factor-α (anti-TNFα) antibody, have demonstrated clinical efficacy and safety as induction and maintenance therapies in patients with moderate to severely active ulcerative colitis (UC). This study aimed to evaluate the efficacy and safety of golimumab as maintenance therapy in the Japanese population. MethodsIn this phase 3, double-blind (DB), placebo-controlled, parallel group, randomized withdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 17 publications
2
62
3
Order By: Relevance
“…The current work extends our previously published systematic review and network meta‐analysis, which searched for data through December 2013, by adding one more treatment comparator in the network (ie tofacitinib) and using a much broader evidence base (ie 3 more RCTs of biologics published after 2014 and 4 RCTs of tofacitinib), and provides updated evidence to inform patient management decisions.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The current work extends our previously published systematic review and network meta‐analysis, which searched for data through December 2013, by adding one more treatment comparator in the network (ie tofacitinib) and using a much broader evidence base (ie 3 more RCTs of biologics published after 2014 and 4 RCTs of tofacitinib), and provides updated evidence to inform patient management decisions.…”
Section: Discussionmentioning
confidence: 82%
“…Figure summarises the evidence search and selection process. Thirteen full‐text publications reported the results of 19 eligible studies (ACT 1; ACT 2; ULTRA 1, ITT‐A3; ULTRA 1, ITT‐E; ULTRA 2; Study A3921063; GEMINI 1, induction; GEMINI 1, maintenance; PURSUIT‐SC, phase 3; PURSUIT‐SC, phase 2; PURSUIT‐SC, phase 2 additional; PURSUIT‐M; Suzuki et al. ; Jiang et al.…”
Section: Resultsmentioning
confidence: 99%
“…From a total 1866 unique studies identified using our search strategy, we included 12 RCTs of first‐line agents (in biologic‐naïve patients), (ACT 1 and 2, Jiang et al, NCT01551290, ULTRA 1 and 2, Suzuki et al, PURSUIT, GEMINI I, OCTAVE 1 and 2) and 4 of second‐line agents (in patients with prior anti‐TNF exposure), in patients with moderate‐severe ulcerative colitis (ULTRA 2, GEMINI I, OCTAVE 1 and 2). Trials of infliximab (ACT 1 and 2, Jiang et al, NCT01551290,), adalimumab (ULTRA 2, Suzuki et al) and vedolizumab (GEMINI I) also reported outcomes on maintenance therapy, within the same publication; PURSUIT‐M, PURSUIT‐J and OCTAVE‐SUSTAIN reported outcomes for maintenance therapy with for golimumab and tofacitinib respectively . The schematic diagram of study selection is shown in Figure S1 and available direct comparisons and network of trials are shown in Figure and (and Figure S2A and S2B).…”
Section: Resultsmentioning
confidence: 99%
“…Through the selection process presented in flow diagram in Figure , we identified 38 records corresponding to 16 randomised placebo‐controlled trials (4728 patients) (Table S2). Two studies (NCT01551290, PURSUIT‐J) provided incomplete data on HRQL outcomes and could not be included in the meta‐analysis. Thirteen trials assessed impact on HRQL during induction therapy with infliximab (n = 3, ACT1, ACT2, Probert 2003), adalimumab (n = 3, ULTRA 1, ULTRA 2, Suzuki 2014), golimumab (n = 3, PURSUIT‐SC [phase 2, phase 2 additional, phase 3]), vedolizumab (n = 1, GEMINI 1) and tofacitinib (n = 3, Sandborn 2012, OCTAVE 1, OCTAVE 2).…”
Section: Resultsmentioning
confidence: 99%
“…Through the selection process presented in flow diagram in Figure 1, we identified 38 records corresponding to 16 randomised placebo-controlled trials (4728 patients) (Table S2). Two studies (NCT01551290, PURSUIT-J) 25,26 provided incomplete data on HRQL outcomes and could not be included in the meta-analysis. Thirteen trials assessed impact on HRQL during induction therapy with infliximab (n = 3, ACT1, 27 ACT2, 27 (Table S3).…”
Section: Study Selection-characteristics Of Included Studiesmentioning
confidence: 99%